Study of External Measurements of Heart in Adult Bangladeshi Population - Shirin, Lubna; Naushaba, Humaira; Kabir, Mohammad Shahjahan; Rahman, SM Niazur; Yasmin, Tahmida; Alam, Tanbira; Faruque, Md (University Heart Journal, 2015)
The knowledge regarding normal physical measurement of heart is very important for proper diagnosis and management of various cardiac diseases. Heart disease is a predominant cause of disability and death among all industrialized nations. This study is to establish a standard data of different external parameters of heart of adult Bangladeshi population. The study was conducted at Department of Anatomy, Sir Salimullah Medical College, Dhaka from July 2009 to December 2009. The formalin fixed cadaveric 60 (sixty) (n=60) human hearts, 41 (forty one) male and 19 (nineteen) female were taken. The length, breadth and weight of the heart were measured and the data was analyzed statistically. The mean value of the length of the heart in male was 10.35±0.62 cm and female was 10.22±0.90 cm. The mean value of the breadth of the heart was 7.45±0.73 cm and 7.35±0.65 cm in male and female respectively. The mean value of the weight of the heart was 174.15±15.49 gm in male, where as for female the mean was 171.58±19.16 gm. The comparison of values of above mentioned variables between male and female were done by unpaired students test and it was statistically not significant. University Heart Journal Vol. 10, No. 2, July 2014; 78-80